ANALISIS PROYEKSI TIMBULAN SAMPAH DAN KEBUTUHAN FASILITAS PENGELOLAAN SAMPAH KOTA PADANG TAHUN 2026–2029 BERDASARKAN PERTUMBUHAN PENDUDUK - Vina Azatri; Nurmeizon Saleh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Population growth is one of the main factors contributing to the increase in municipal solid waste generation. Padang City, as the capital of West Sumatra Province, has experienced rapid development in residential, commercial, educational, and service sectors, resulting in a growing demand for waste management services. This study aims to analyze population growth projections, estimate municipal solid waste generation, and evaluate the future demand for waste management facilities in Padang City for the period 2026–2029. A quantitative descriptive approach was employed using secondary data on population and municipal solid waste generation from 2022 to 2025. Population projection was estimated using the geometric growth method, while waste generation was projected based on per capita waste generation. The projected waste generation was then compared with the existing waste management facilities to evaluate future infrastructure requirements. The results indicate that the population of Padang City is projected to increase from 965,050 people in 2025 to approximately 1,029,526 people in 2029, with an average annual growth rate of 1.63%. Consequently, municipal solid waste generation is projected to increase from 244,179.26 tons/year in 2025 to approximately 257,407 tons/year in 2029, with an average per capita waste generation of 0.685 kg/person/day. Existing waste management facilities consist of 127 temporary waste collection sites (180 units), 11 dump trucks, 19 arm roll trucks, 175 waste banks, and the Aia Dingin Landfill covering 33 hectares with a capacity of 4–4.8 million tons. Increasing waste generation requires optimization of waste collection systems, expansion of waste management facilities, strengthening of waste bank programs, and development of waste treatment facilities to support sustainable municipal solid waste management. The findings of this study are expected to provide valuable input for future waste management planning in Padang City.Keywords: population projection, municipal solid waste, waste management facilities, waste management, Padang City